Crashworthiness optimal design of a new extruded octagonal multi-cell tube under dynamic axial impact. (2018) - Bai, Zhonghao; Sun, Kai; Zhu, Feng; Cao, Libo; Hu, Jun; Chou, Clifford C.; Jiang, Binhui
A new extruded octagonal multi-cell tubular energy absorber is developed for improving and enhancing the vehicle crashworthiness. A combined experimental and numerical study is conducted to further assess its performance. In this study, a sled impact test is first performed to investigate the structural response of an octagonal multi-cell tube, and the test data are then used to validate the FE tube model. Using this FE tube model, the effect of key geometric parameters on the structural crashworthiness is analysed in detail. It is found that the number of webs along the circumferential direction, the size of inner tube and wall thicknesses of outer tube, web and inner tube have significant effects on crashworthiness of the energy absorber mentioned above. Based on the parametric study, multi-objective optimisation is subsequently performed to further improve its energy absorption efficiency. These findings can provide valuable guidelines for designing such new types of energy absorber under dynamic axial impact.